(untitled) (INTEK : Jurnal Informatika dan Teknologi Informasi, 2025)
The advancement of communication technology has progressed rapidly in recent years. One prominent example of this technology is the smartphone, which serves as a primary communication tool for many people. Smartphones are compact devices designed to provide users with access to information anytime and anywhere. Therefore, a Decision Support System (DSS) is needed to assist in eval_uating and selecting smartphones based on several criteria such as RAM, storage capacity, color, and price. The TOPSIS method (Technique for Order Preference by Similarity to Ideal Solution) is implemented to help prospective buyers identify the most suitable smartphone according to their preferences. This study involved several stages, including data collection from Kaggle, data preprocessing, determining alternatives and criteria, processing with the TOPSIS method, and system eval_uation. The eval_uation results revealed that the use of 237 smartphone alternatives led to a slowdown in the TOPSIS processing phase when displaying results on the website. Despite this challenge, the system proved effective in assessing and ranking smartphones. Among all alternatives, the Realme 11 Pro 12/512/Black was identified as the best choice, with a preference value of 0.8251.